Academic Health Centers and the Quintuple Aim of Health Care. (18th October 2022) - Farrell, Timothy W.; Greer, Annette G.; Bennie, Scott; Hageman, Heather; Pfeifle, Andrea
Abstract : The Quintuple Aim of health care adds health equity to the existing Quadruple Aim of improving the individual experience of care for patients, improving the health of populations, reducing the per capita cost of care, and improving the experience of health care professionals. Health equity has previously been subsumed within the other 4 aims. Elevating health equity to the status of a distinct aim is necessary to address persistent health inequities that disproportionately affect underrepresented and minoritized groups. Academic health centers (AHCs) bear a unique responsibility to advance health equity due to the societal importance of their 4 missions: patient care, education, research, and community collaboration. Interprofessional education and practice provide natural connection points that enable AHCs to prepare both health professions students and practicing health care professionals to address all 5 aims. AHCs are well positioned to assess health outcomes related to health equity, develop a health care workforce that is representative of their communities, develop innovative research questions regarding health equity, and engage and invest in the communities they serve.